The consolidation policy of the democratic security: balance 2006-2008 (2009)
The following lines are aimed at making a balance of the Consolidation Policy of the Democratic Security (PCSD for its acronym in Spanish) in its first two years of application that is, between 2006 and 2008. For this, we turn to the analysis of the central policy topics: official statistics reviewing and comparing; registered results and impacts facing public opinion, current state of the war against the insurgency groups, the war against paramilitaries, forced displacement, the strategy against drugs, the human rights situation, and the accrual costs and investments. Such topics are observed under the doctrinarian conception of the PCSD in general as well as in relation with its implications and concrete results.